Immune response and protective efficacy of the SARS-CoV-2 recombinant spike protein vaccine S-268019-b in mice - Homma, Tomoyuki; Nagata, Noriyo; Hashimoto, Masayuki; Iwata-Yoshikawa, Naoko; Seki, Naomi M.; Shiwa-Sudo, Nozomi; Ainai, Akira; Dohi, Keiji; Nikaido, Eiji; Mukai, Akiko; Ukai, Yuuta; Nakagawa, Takayuki; et al. (Scientific reports, 2022)
Vaccines that efficiently target severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the etiological agent for coronavirus disease (COVID-19), are the best means for controlling viral spread. This study evaluated the efficacy of the COVID-19 vaccine S-268019-b, which comprises the recombinant full-length SARS-CoV-2 spike protein S-910823 (antigen) and A-910823 (adjuvant). In addition to eliciting both Th1-type and Th2-type cellular immune responses, two doses of S-910823 plus A-910823 induced anti-spike protein IgG antibodies and neutralizing antibodies against SARS-CoV-2. In a SARS-CoV-2 challenge test, S-910823 plus A-910823 mitigated SARS-CoV-2 infection-induced weight loss and death and inhibited viral replication in mouse lungs. S-910823 plus A-910823 promoted cytokine and chemokine at the injection site and immune cell accumulation in the draining lymph nodes. This led to the formation of germinal centers and the induction of memory B cells, antibody-secreting cells, and memory T cells. These findings provide fundamental property of S-268019-b, especially importance of A-910823 to elicit humoral and cellular immune responses.